Not the future we ordered : peak oil, psychology, and the myth of progress - Greer, John Michael (Karnac Books, 2013)
For well over half a century, since the first credible warnings of petroleum depletion were raised in the 1950s, contemporary industrial civilization has been caught in a remarkable paradox: a culture more focused on problem solving than any other has repeatedly failed to deal with, or even consider, the problem most likely to bring its own history to a full stop. The coming of peak oil--the peaking and irreversible decline of world petroleum production--poses an existential threat to societies in which every sector of the economy depends on petroleum-based transport, and no known energy source can scale up extensively or quickly enough to replace dwindling oil supplies. Resolute action on personal, local, national, and global levels over the decades just passed might have staved off a future of economic contraction, political turmoil, and immense human suffering. Instead, governments and populations of all the world's industrial nations collectively closed their eyes to the impending crisis.